Parametric investigation of polymethacrylate monolith synthesis and stability via thermogravimetric characterisation - Acquah, C.; Danquah, Michael; Loo Chin Moy, Charles; Anwar, M.; Ongkudon, C. (John Wiley & Sons, Ltd, 2017)
Polymethacrylate monoliths are synthetic adsorbents with macroporous and mesoporous interconnected channels that can be engineered to target the hydrodynamic features of a wide range of molecular species. However, rigorous study into the effect of synthesis conditions on their thermal stability is limited. This work attempts to characterise the influence of key synthesis process variables on the stability of polymethacrylate monoliths using thermogravimetric analysis at a heating rate of 10 °C/min. Experimental results showed that the thermal stability of polymethacrylate monoliths increased with decreasing polymerisation temperature from 85 to 65 °C. Increasing the total porogen (P) to monomer (M) ratio increased the thermal stability of the monolith by >62% and >50% for P40/M60-P60/M40 and P60/M40-P80/M20, respectively. The impact of the initiator concentration, monomer variation, biporogen ratio, washing and activation of the monoliths was investigated. Nuclear magnetic resonance analyses conducted confirmed the hydrolysis of epoxy moieties on the monolith.